1992
DOI: 10.1002/mc.2940060209
|View full text |Cite
|
Sign up to set email alerts
|

Kinds of mutations induced by aflatoxin B1 in a shuttle vector replicating in human cells transiently expressing cytochrome P450IA2 cDNA

Abstract: Transient expression of rat liver cytochrome P450lA2 cDNA was combined with the use of a shuttle vector as a mutational target to determine the frequency and types of mutation caused by the conversion of aflatoxin B1 into genotoxic metabolites within human cells. Ad293 cells were first transfected with p91-lA2, a rat liver P450lA2 cDNA expression vector, or with p91-lA2(i) (a control vector that has the P450 cDNA in the inverted orientation) and incubated for 24 h to permit P450lA2 accumulation. Cells were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The predominant mutation of AFB1-N7-Gua (Fig. 3) was the G -*> T transversion (-75% of all mutations), similar to that observed previously with metabolically activated AFB1 in E. coli induced for the SOS response and containing the mucAB mutagenesis-enhancing gene products (13) and in mammalian systems (16,22). A possible premutagenic lesion responsible for this mutation is the AP site that results from the facile depurination of AFB1-N7-Gua.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The predominant mutation of AFB1-N7-Gua (Fig. 3) was the G -*> T transversion (-75% of all mutations), similar to that observed previously with metabolically activated AFB1 in E. coli induced for the SOS response and containing the mucAB mutagenesis-enhancing gene products (13) and in mammalian systems (16,22). A possible premutagenic lesion responsible for this mutation is the AP site that results from the facile depurination of AFB1-N7-Gua.…”
Section: Discussionsupporting
confidence: 84%
“…Both GC --TA and GC --AT mutations are induced with equal efficiency in other systems by metabolically activated AFB1 (14) and AFB1 8,9-dichloride (15) (16,17). In the c-Ki-ras oncogene of rat hepatocellular carcinomas, GC -> AT transitions in codon 12 are observed (18,19 (20,21).…”
mentioning
confidence: 99%
“…AFB1 and BPDE are well-studied genotoxic carcinogens that are known to cause point mutations (Foster et al, 1983;Trottier et al, 1992b;Levy et al, 1992;Yang et al, 1987;Wei et al, 1991Wei et al, , 1993. Although CPBA is a known DNA-damaging agent (Jacobsen and Humayun, 1986;Rosenthal et al, 1990), its mutagenic properties seem not to have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…1 Dietary exposure to aflatoxins has liver by microsomal oxidase to reactive AFB 1 (8,9-epoxide) that is covalently linked to DNA, inducing mutation of the p53 gene at codon 249 (p53 mt 249), a critical factor in the development of hepatocarcinoma. [5][6][7][8] Aflatoxins also cross the placenta and high concentrations have been found in cord blood, 3,9 thereby affecting the fetus and newborn. It has been reported to be a risk factor for jaundice in the newborn.…”
Section: Introductionmentioning
confidence: 99%